PENGELOLAAN SAMPAH RUMAH TANGGA BERBASIS MASYARAKAT DI KELURAHAN BATU PIRING KECAMATAN PARINGIN SELATAN KABUPATEN BALANGAN - Raudah, Siti; Amalia, Risna; Nida, Khairun (PPPM STIA Amuntai, 2022)
The management of household waste in Batu Piring Village is still constrained by public awareness, lack of communication and the lack of cooperation between the government, the community and other agencies. The purpose of this study is to determine Community-Based Household Waste Management in Batu Piring Village, Paringin Selatan District, Balangan Regency. The method used is descriptive qualitative research, namely descriptive research where the author wants to try to describe the situation that appears in the field as it is, in accordance with the reality and state of the object under study at the time the research was conducted based on the facts in the field. With 12 informants, the technique used is maximum variety sampling. and data collection techniques, namely interviews, observation and documentation The results of the study indicate that community-based household waste management in Batu Piring Village, Paringin Selatan District, Balangan Regency is still not optimal, this can be seen from the indicators, namely First; Thoughts (psychological participation) which are divided into 2 indicators, namely ideas and initiatives are still not optimal, Second; Physical participation, namely the active role of the community is also not fully operational. Third; Thoughts and energy (psycholigical and physical participation) there are 2 indicators, namely planning programs that are not optimal and implementing programs in managing household waste which are also not optimal and Fourth; Goods (participation materials) are supporting tools such as a garbage chopper and a cardboard press machine as well as facilities for processing and sorting waste. Meanwhile, the other 3 indicators have been running well. The driving factor is the socialization 4 times a year that is once every three months, the inhibiting factors are ideas, initiatives and the active role of the community that is not optimal due to the lack of public awareness in sorting waste, the lack of communication in planning the program, the lack of cooperation in implementing the program, and the absence of supporting tools such as a garbage chopper and a tool to press cardboard and plastic. The efforts of the local government to provide socialization and guidance on the management of household waste in the Batu Piring sub-district to make it better and raise public awareness. The suggestions given for input materials are being more active in coaching to manage waste, adding supporting tools such as press machines, establishing communication and cooperation between the government, the community and other agencies.